USE OF CAPS SCRAPBOOK MEDIA TO INCREASE STUDENTS' LEARNING MOTIVATION IN LEARNING FIKIH ALMS MATERIAL FIFTH GRADES - Kasanah, Agustin Arianti Uswatun; Hibatullah, Mahbubah Lihani; Mala, Asnal (PROGRES PENDIDIKAN, 2024)
This research explains how scrapbook learning media is used to increase student learning motivation in learning jurisprudence in grade 5 students at SD/MI. The method used in this research is literature study. The conclusion in this research is that by using the Caps Scrapbook learning media to increase students' learning motivation in class 5 SD/MI fiqh learning, it can be concluded that using the Caps Scrapbook learning media can increase students' learning motivation, apart from increasing students' learning motivation, it can also make students become more active in learning. Caps scrapbook learning media is an alternative that can be used as a learning media that is not only fun but also effective. Scrapbook caps are a flexible learning medium because they can be applied in any subject and at any level. The conclusions of this research are proven from various research results of other people that have been carried out previously.